Chang’E-5 radar reveals fast regolith production at landing site - Gang Yu; Yong Pang; Menglong Xu; Yuqi Qian (Scientific Reports)
Abstract Lunar regolith is an unconsolidated fine-grained layer overlaying on the entire lunar surface, formed by continuous impact and space weathering processes. The production of lunar regolith is both related to the protolith internal properties and the external gardening primarily modulated by impact flux. The penetrating radar data of Chang’E-5 is used to investigate the subsurface structures and the production and evolution of lunar regolith at the landing site. Together with the penetrating radar results from Chang’E-3, we found that the regolith production rates on the ejecta blanket of fresh craters are faster than Apollo sites. The speed up of the regolith production for Chang’E-3 and Chang’E-5 sites may be due to the increased impact flux during the recent history of the solar system, that also recorded by the impact beads and the fragile nature of the ejecta blanket at the two sites. The result of this article can be highly beneficial to the radar signal processing and further explanation of Chang’E-6.